THE APPLICATION OF PR COMMUNICATION MODEL IN INVESTOR RELATIONS THROUGH WEB 2.0 - Hanathasia, Mirana (Journal Communication Spectrum : Capturing New Perspectives in Communication, 2012)
Tulisan ini bertujuan untuk menganalisa sejauh mana investor relations bank sebagai bagian  dari perusahaan keuangan di Indonesia menggunakan teknologi Web 2.0 untuk menjangkau para pemangku kepentingannya melalui internet, sejauh mana model komunikasi publicrelations diterapkan untuk berkomunkasi dengan para pemangku kepentingan melalui  internet, dan sejauh mana komunikasi melalui website akan mempengaruhi pemangku kepentingan dalam pengambilan keputusan investasi.  Objek dalam penelitian ini adalah tiga institusi keuangan –bank yang terdaftar di Bursa Efek Indonesia. Metode penelitianadalah kualitatif dan klasifikasi penelitian berdasarkan tujuannya adalah penelitian deskriptif. Wawancara mendalam terhadap tiga Investor Relations Head dari bank pemerintah dilakukan. Hasil penelitian menunjukkan bahwa model komunikasi yang  dilakukan oleh institusi keuangan terhadap para pemangku kepentingan melalui website  investor  relations adalah satu arah dan penggunaan teknologi Web 2.0 belumlah optimal. Namun, pada dasarnya komunikasi dua arah sudah dilaksanakan oleh staff investor  relations melalui Komunikasi yang lebih personal melalui telepon/conference  call, surat elektronik, dan pertemuan tatap muka. Simpulannya, penerapan model komunikasi public   relations dalam aktivitas investorrelations melalui teknologi Web 2.0 hanya sekedar untuk penyebaran informasi saja belum sampai tahap memengaruhi pemangku kepentingan dalam pengambilan keputusan investasi. Kata kunci: internet, website, teknologi Web 2.0, investor  relations, institusi finansial.   This paper aims to analyze the extent to which investor relations of  financial institutions in Indonesia are using Web 2.0 technologies in order to reach their stakeholders through internet,  the  extent  to  which  public  relations  communication  model  applied  in communicating  with  stakeholders  through  internet, and  the  extent  to  which  the communication via website will influence stakeholders to have the investing decision. The objects of this research are three banks as financial institutions listed on Indonesia Stock Exchange. The method is  a qualitative research  and the nature of this research is descriptive. Depthinterview was held by interviewing three Investor Relations Heads of state banks. The result of this research shows that the communication model applied from financial institution to its stakeholders on investor relations Website is oneway and the use of Web 2.0 technologies in banks has not been maximum. Moreover, the information on the website does not influence the stakeholders in making investment decision. However, twoway communication is managed personally, through phone/conference call, email, and oneon one meeting. In conclusion, the application of public relations communication model for the investor relations activities in Indonesia through the usage of Web 2.0 technologies is is only to disseminate information, not to persuade stakeholders in making investment decision. Keywords: internet, website, Web 2.0 technology, investor relations, financial institution.